Investigation of combustion-induced vibration sources in a diesel engine in the time-frequency domain using the wavelet analysis method and wavelet cross-correlation analysis method - Natsuki Takahashi; Shun Nakagawa; Masato Mikami (Measurement: Energy)
This study investigated the characteristics of in-cylinder pressure and vibration acceleration for a single-cylinder diesel engine for different engine speeds using three analysis methods: FFT analysis, wavelet analysis, and wavelet cross-correlation analysis. The cross-correlation coefficients between the in-cylinder pressure and the vibration acceleration of the outer wall near the combustion chamber in the 1/3-octave band were examined to determine whether there was any engine speed dependency and what vibration-transmission characteristics were present. The results from the engine speed dependency suggest that the vibration at 2500 Hz is caused by the piston-connecting rod coupled vibration, which is one of the natural frequencies of the engine, the vibration at 8000 Hz is caused by a combustion chamber resonance, at 6300 Hz a combustion chamber resonance may be linked with a piston natural vibration, and a piston slap may cause the vibration at 5000 Hz. These analysis methods are useful for predicting the source of combustion-induced vibration.